La koinonía en Platón - Mesquita, Antonio Pedro (2018)
This paper aims to defend the unitarian position of Plato’s thought through an analysis of the Sophist in its relation with other middle and late dialogues. Contrary to those who consider that koinonia is an exclusive philosophical motif of the late period and represents a break with the dialogues of the intermediate period, the text seeks to defend how koinonia in the Sophist is not a rupture but a development and a consummation of Platonic positions sustained since the middle dialogues.